Synthesis and physical evaluation of urea- and thiourea-based receptors and sensors for anions - Ali, Haslin Dato Paduka Haji (Trinity College (Dublin, Ireland). School of Chemistry, 2007)
This thesis, entitled “Synthesis and Physical Evaluation of Urea- and Thiourea-based Receptors and Sensors for Anions”, consists of five chapters. Chapter 1 briefly introduces the field of molecular sensing, followed by a general description of anion sensing, which includes the design principles of anion receptors and sensors as well as the advantages of their practical use. A review of various recent examples of urea- and thiourea-based fluorescent and colorimetric anion sensors is also presented, which is then followed by a summary of the anion sensing work carried out within the Gunnlaugsson research group. Finally, an outline of the project objectives is described. Chapter 2 discusses the synthesis of bis-phenyl urea and thiourea receptors, substituted at the 2- and 4-position of the aromatic rings by electron-donating (i.e. CH3 ) and electron-withdrawing (i.e. F, CF3 ) groups. .... In Chapter 3, the synthesis of polyaromatic thiourea-based fluorescent anion sensors is described and the physical evaluation of their anion binding abilities in DMSO or DMSO-d6 using various techniques (such as 1H NMR, fluorescence and CD spectroscopies) is discussed. ... Chapter 4 concentrates of the synthesis and anion binding studies of hydrazinebased naphthalimide colorimetric sensors, consisting of either a urea or thiourea moiety. ... Finally, Chapter 5 outlines the experimental procedures used in Chapter 2-4, and presents the characterisation of the compounds prepared.
Keywords: Chemistry, Ph.D.; Ph.D. Trinity College Dublin